Perfectionism and achievement goals in young Finnish ice-hockey players aspiring to make the Under-16 national team - Stoeber, J.; Stoll, O.; Salmi, O.; Tiikkaja, J. (Journal of Sports Sciences, 2009)
Research on perfectionism suggests that is it useful to differentiate between perfectionistic strivings and perfectionistic concerns. Regarding the 2 2 achievement goal framework, the usefulness of this differentiation was recently demonstrated in a study with university student athletes (Stoeber, Stoll, Pescheck, & Otto, 2008, Study 2), in which it was found that perfectionistic strivings were associated with mastery-approach and performance-approach goals and perfectionistic concerns with mastery-avoidance, performance-approach, and performance-avoidance goals. Because the study was largely exploratory and only used non-elite athletes, the aim of the present research was to replicate and extend these findings by investigating a sample of 138 young, elite ice-hockey players, while adding further measures of perfectionism and using structural equation modelling (SEM) to confirm the relationships between perfectionistic strivings, perfectionistic concerns, and the 2 2 achievement goals. The SEM results showed that, in elite athletes also, perfectionistic strivings are associated with mastery-approach and performance-approach goals, whereas perfectionistic concerns are associated with mastery-avoidance, performance-approach, and performance-avoidance goals. Our findings corroborate the importance of differentiating between perfectionistic strivings and perfectionistic concerns when studying perfectionism in sports, because only perfectionistic concerns (and not perfectionistic strivings) are associated with maladaptive patterns of achievement goals.